Factors affecting the Survival of Soft Tissue Sarcoma Patients of the Extremities at Cipto Mangunkusumo Hospital, Indonesia - Yulian, Erwin D; Sinaga, Kezia M.; Kartini, Diani; Kekalih, Aria (The New Ropanasuri Journal of Surgery, 2023)
Introduction. The strategy for treating limb soft tissue sarcoma (STS) is challenging due to delayed diagnosis and the non-specific clinical picture, leading to the mortality of nearly 50% of newly diagnosed patients. Various therapeutic modalities have been applied to increase the survival of patients with extremity soft tissue sarcoma. However, clinicopathological factors can influence the survival rate and thus affect the effectiveness of therapy. This study aims to determine the numbers and factors influencing overall survival five years after treatment for patients with soft tissue sarcoma of the extremities at Dr. Cipto Mangunkusumo General Hospital (CMGH) in 2011-2015. Method. A prognostic study was run on patients with complete histopathology who underwent treatment during 2011-2015. Data analysis using the Kaplan-Meier method, cox regression test, and Cox regression with time-dependent variable. Results. A total of 42 were enrolled in the study. The median survival after therapy for patients was six years (3 months – 8.25 years), with a five-year survival of 52.4%. Factors affecting five-year survival were surgical procedures in limb-saving surgery (HR 0.852 95% CI 0.68 – 1.07, p = 0.163). Conclusion. The five-year survival rate of soft tissue sarcomas of the extremities was 52.4%. Overall survival is affected by higher-grade sarcoma, incomplete therapy, and worse clinical stage.